Familial abnormalities of thyroxine binding proteins: some problems of recognition and interpretation. Issue 3 (March 1985) - Neild, J E; Byfield, P G; Lalloz, M R; Tait, D; Marigold, J H; Croft, D N; Slavin, B M
Abstract : A three generation family study was carried out after inappropriate treatment with radioactive iodine of a 50 year old woman with a raised serum total thyroxine concentration and free thyroxine index. Subsequent investigations showed that she and five members of her family had raised thyroxine binding globulin concentrations. Free thyroxine and free triiodothyronine concentrations were normal. Problems encountered in the recognition of this thyroxine binding protein disorder are discussed. Clinicians and clinical biochemists should be aware of these pitfalls and thus avoid further incorrect treatment on the basis of biochemical findings, even though free hormone estimations are now becoming readily available.